Modulation of urethral alpha-sympathetic by parasympathetic before and following bethanechol chloride injection - Suaid,Haylton J. (2003)
INTRODUCTION AND OBJECTIVES: Chagas' disease causes specific parasympathetic denervation and in its digestive clinic form promotes also functional alterations in bladder. Thus, the aim was to investigate the existence of balance between sympathetic and parasympathetic systems in lower urinary tract, as occurs in other organs. We verified the urethral closing pressure before and following parasympathetic stimulus. PATIENTS AND METHODS: For that, the urethral closure pressure was studied before and after the injection of 5 mg of bethanechol chloride subcutaneously in 28 voluntary female patients, divided into 4 groups. The constitution of theses groups was: A) normal control = 6 patients; B) Chagas' disease with positive serology only = 5 patients; C) Chagas' disease with cardiac disease = 6 patients, and D) Chagas' disease with digestive disease and vesical hyporeflexia = 11 patients. Urethral profilometry was performed through perfusion urethral catheter with a 6.5 ml/minute flow and a traction rate of 5 mm/minute. RESULTS: Means and standard deviations for urethral closure pressure before bethanechol chloride were respectively: group A = 67.3 ± 7.1; group B = 69.2 ± 7.4; group C = 95.8 ± 5.1; group D = 82.1 ± 8.4. After bethanechol chloride they were: group A = 66.0 ± 6.6; group B = 77.0 ± 7.6; group C = 98.3 ± 8.8; group D = 45.9 ± 6.2. The Kruskal Wallis statistical test did not show statistically significance difference between groups A, B, C. However, it was statistically significant between groups C and D with p = 0.003. Wilcoxon test showed p = 0.001, only for values in group D before and following bethanechol chloride. CONCLUSIONS: Chagas' disease in its intestinal form seems to alter urethral function as well. Parasympathetic stimulation decreased urethral pressure, indicating potential modulation by the parasympathetic system over the sympathetic system.